Proses Mediasi Perkara Perceraian Di Peradilan Agama - Mustakid, Dodo (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2020)
To overcome the problems of the ineffective and inefficient justice system, an alternative settlement of disputes with peace has emerged. Obligation of mediation, especially in marital disputes such as divorce, will bring great benefits to the parties, because through mediation agreements will be reached that will satisfy and resolve the problems that cause the rift of the household so that the integrity of the household is maintained. However, it should be remembered, that marital disputes (divorce) submitted to the court is not uncommon at the time of the trial that has been determined only attended by one party, namely the Plaintiff / Petitioner or Defendant / Respondent, while the other parties do not know the exact address. This is where the problem arises, whether the trial is adjourned to summon the Defendant / Respondent or parties not present as Article 127 HIR / 151 RBg, or postponed for mediation. Abstrak Untuk mengatasi problematika sistem peradilan yang tidak efektif dan efisien tersebut, maka muncul alternatif penyelesaian sengketa dengan perdamaian. Diwajibkannya mediasi khususnya dalam sengketa perkawinan seperti perceraian membawa manfaat yang besar bagi para pihak, karena melalui mediasi akan dicapai kesepakatan dan solusi yang memuaskan dan terselesaikannya problem yang menjadi penyebab keretakan rumah tangga sehingga keutuhan rumah tangga tetap terjaga. Namun perlu diingat, bahwa sengketa perkawinan (perceraian) yang diajukan ke Pengadilan tidak jarang pada saat persidangan yang telah ditentukan hanya dihadiri oleh satu pihak saja yaitu pihak Penggugat/Pemohon atau Tergugat/Termohon, sedangkan pihak lainnya tidak diketahui alamat pastinya. Di sinilah akan muncul permasalahan, apakah persidangan ditunda untuk memanggil Tergugat/Termohon atau pihak yang tidak hadir sebagaimana Pasal 127 HIR/151 RBg, atau ditunda untuk mediasi.